2019
DOI: 10.4038/slja.v27i2.8416
|View full text |Cite
|
Sign up to set email alerts
|

Combined Platelet Rich Plasma Intra-articular Shoulder Injection and Stellate Ganglion block, A new Technique for Management of Chronic Post-mastectomy Shoulder Pain Syndrome: A randomized Controlled Trial.

Abstract: Background: Adhesive capsulitis of the shoulder is common after breast cancer treatment. We aimed to compare the effects of using stellate ganglion block (SGB) with bupivacaine and ketamine alone versus its combined use with intra-articular platelet rich plasma (PRP) injection in patients with post-mastectomy shoulder pain. Methods: A prospective randomized open blinded end-point pilot study was conducted in Mansoura University Oncology Center, Egypt during the period from August 2017 till April 2018. Sixty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Accordingly, potential studies were initially detected, and following a layer-by-layer screening, one prospective study and three randomized trials were included in the final quality assessment and data extraction. Of the four studies [17][18][19][20], three reported a VAS (n = 295) while three reported a ROM (n = 299). The literature screening process and results are shown in Fig.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, potential studies were initially detected, and following a layer-by-layer screening, one prospective study and three randomized trials were included in the final quality assessment and data extraction. Of the four studies [17][18][19][20], three reported a VAS (n = 295) while three reported a ROM (n = 299). The literature screening process and results are shown in Fig.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…Sequence generation and allocation were adequately reported by two studies [18,19], except for one study [17] where the concealment of allocation from the investigators and sequence generation was unclear (unclear risk of bias). Two studies [18,19] were considered at a low risk for detection bias because of the blinding of the outcome assessor, except for one study [17] in which the outcome assessor was not reported (unclear risk of bias). Patients in two studies [18,19] were blinded to their intervention group (low risk of bias), except for one study [17] in which the patients were not blinded to their intervention group (unclear risk of bias).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Barman et al [ 8 ] compared one injection of PRP to an injection of Methylprednisolone 2cc + 2cc of 2% Lidocaine. Ghaffar et al [ 25 ] compared three injections of PRP + Stellate Ganglion Block + Ketamine + 5 cc Bupivacaine 0.5% + 10 cc Saline to the same regimen without PRP. Kothari et al [ 7 ] looked at one injection of PRP with either an injection of 2 cc methylprednisolone or ultrasound therapy.…”
Section: Reviewmentioning
confidence: 99%
“…In terms of the control groups, Table 1 above shows the wide variation in control methods ranging from no intervention to injection of Stellate Ganglion Block + Ketamine + 5cc Bupivacaine 0.5% + 10cc Saline [ 25 ]. Multi-faceted control groups can make it hard to directly compare results.…”
Section: Reviewmentioning
confidence: 99%